2012
DOI: 10.1111/j.1758-5910.2011.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical laparoscopic surgery using GelPort through an umbilical zigzag skin incision

Abstract: We developed an umbilical zigzag skin incision technique to perform abdominal laparoscopic operations using a GelPort, with a minimal number of skin incisions. We consider that our method reduces the technical difficulties associated with laparoscopic surgery and maintains cosmesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 8 publications
(15 reference statements)
0
27
0
Order By: Relevance
“…Therefore, the shorter length of the umbilical incision does not increase the difficulty of RPS in terms of laparoscopic handling. Fujii et al (13) reported that the median length of the skin incision was 3.3 cm in SILS for CRC, and Hachisuka et al (14) reported on the zigzag skin incision in RPS for CRC. An incision was required from above to below the umbilical ring.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the shorter length of the umbilical incision does not increase the difficulty of RPS in terms of laparoscopic handling. Fujii et al (13) reported that the median length of the skin incision was 3.3 cm in SILS for CRC, and Hachisuka et al (14) reported on the zigzag skin incision in RPS for CRC. An incision was required from above to below the umbilical ring.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report described that a zigzag incision in the umbilical region had clinical values resembling our procedures but required collaboration with plastic surgeon for keeping aesthetics after surgery. 17 Meanwhile, a Z-shaped incision is simple procedure without requiring any collaboration with a plastic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Resected specimens can be removed through the umbilical skin incision, after which anastomosis can be performed. The umbilical zigzag skin incision was first developed to create a 6-cm fascial and peritoneal opening for performing abdominal laparoscopic procedures [21]. We adopted both the umbilical zigzag skin incision and use of an access device to maintain the pneumoperitoneum during laparoscopic colectomy via reduced port surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The skin was cut along a zigzag line marked in the umbilical region (fig. 1a), and the subcutaneous tissue, linea alba, and peritoneum were incised as previously described [21]. A GelPOINT (Applied Medical, Rancho Santa Margarita, Calif., USA) or EZ Access (Hakko, Nagano, Japan) was used as the umbilical access device (fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation